The Multilevel Encryption Model: A review - Mais Irreem Kamal; Laheeb Ibrahim (Al-Rafidain Journal of Computer Sciences and Mathematics)
Multilevel encryption is a system used to protect sensitive data and information with multiple overlapping encryption methods. This system aims to increase the level of security by adding multiple layers of encryption, which makes it more difficult to decrypt the data. When using the multilevel encryption system, different encryption techniques are applied to the data successively. For example, digital encryption algorithms can be used as initial layers to encrypt data, and then the encrypted data is encrypted again using other encryption techniques. This study aims to review study and analyze research and studies in the field of multilevel encryption system and propose a multilevel encryption system to enhance security and protection from cyber threats, to make it difficult for attackers to break all overlapping layers of encryption.